(untitled) (Journal of Atomic and Molecular Sciences, 2021)
We study the ground and the first excited states energies and the transition frequency between the first excited- and the ground-state of strong-coupling polaron in an anisotropic quantum dot. The effects of the electron-phonon coupling strength and the transverse and the longitudinal effective confinement lengths are taken into consideration by using variational method of the Pekar type. It is found that the transition frequency is an increasing function of the electron-phonon coupling strength, whereas the state energies are decreasing one of it. They will increase rapidly with decreasing transverse and longitudinal effective confinement lengths.